Social media influencers and their impact on consumer behavior: a systematic review of the scientific literature - Mendoza Moreno, Viviana Nicole (2023)
This systematic literature review, prepared according to the PRISMA methodology, documents the trends in studies on the impact of social media influencers on consumer behavior in Ibero-America between 2010 and 2020. The bibliographic search with keywords was carried out in the EBSCO, Redalyc, and Scielo databases to guarantee the academic quality of the articles. Filters were applied to meet the eligibility criteria for selecting Spanish-language articles published during 2010-2020 and related to the research topic. A thorough two-stage review process of the articles was carried out before their final selection, which was systematized in an Excel table. The techniques of concept maps and summary sheets were applied to synthesize the information of the studies selected in an organized way. The articles chosen allowed systematizing the trends into four categories, which address the characteristics of the influencer, their relationship with consumer behavior, the effects of influencer marketing, and the factors that weaken the effectiveness of the influencer. Finally, some limitations were found, such as the limited number of studies in Spanish and open access.